1994
DOI: 10.1161/01.atv.14.4.557
|View full text |Cite
|
Sign up to set email alerts
|

Effects of linoleate-enriched and oleate-enriched diets in combination with alpha-tocopherol on the susceptibility of LDL and LDL subfractions to oxidative modification in humans.

Abstract: This report describes the effects of feeding linoleate-or oleate-enriched diets to subjects who were concurrently taking 1200 mg/d of a-tocopherol on the susceptibility of low-density lipoprotein (LDL) and buoyant and dense LDL subfractions to oxidation. LDL isolated from subjects who consumed linoleate-enriched diets was more susceptible to copper-mediated oxidation, as measured by formation of conjugated dienes and lipid peroxides and loss of unsaturated fatty acids, compared with LDL isolated from subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
90
3
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(109 citation statements)
references
References 54 publications
13
90
3
3
Order By: Relevance
“…The effects observed on plasma LDL cholesterol and on susceptibility of LDL to oxidation are consistent with those reported in previous studies with MUFA-enriched diets (Mata et al, 1992;Reaven et al, 1994), but these studies were longer (3 -4 weeks). Other studies have also showed that extravirgin olive oil increases resistance to oxidation in animals (Wiseman et al, 1996), in healthy subjects (Carmena et al, 1996), and in subjects with cardiovascular disease (RamirezTortosa et al, 1999).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The effects observed on plasma LDL cholesterol and on susceptibility of LDL to oxidation are consistent with those reported in previous studies with MUFA-enriched diets (Mata et al, 1992;Reaven et al, 1994), but these studies were longer (3 -4 weeks). Other studies have also showed that extravirgin olive oil increases resistance to oxidation in animals (Wiseman et al, 1996), in healthy subjects (Carmena et al, 1996), and in subjects with cardiovascular disease (RamirezTortosa et al, 1999).…”
Section: Discussionsupporting
confidence: 89%
“…In a review, Parthasarathy et al, (1999) explain that the susceptibility of LDL to oxidation depends on the MUFA=PUFA ratio, their oleic acid and antioxidant contents and also on the size of LDL particle. It has been reported (Reaven et al, 1994) that small dense lipoprotein particles are more susceptible to oxidation and that oleic acid promotes the formation of larger particles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the change in n-6 PUFAs in serum phospholipids differed significantly between the groups, but the intragroup increase in linoleic acid during 1 y of corn oil treatment did not reach statistical significance. Several studies support the notion that a high intake of n-6 PUFAs may increase lipid peroxidation (Reaven et al, 1991(Reaven et al, , 1993(Reaven et al, , 1994, and may explain the increase over 1 y also in our control group. Therefore, the choice of control in our study may partly mask the effect of n-3 PUFAs intervention.…”
Section: Discussionsupporting
confidence: 83%
“…Linoleic acidenriched LDL particles are oxidised in vitro faster than LDL particles enriched with saturated or monounsaturated fatty acids (Reaven et al, 1994). Inconsistent in vitro results have been published with respect to both plant and marine n-3 PUFA (Suzukawa et al, 1995;Brude et al, 1997).…”
Section: Health Aspects Of ®Sh and N-3 Polyunsaturated Fatty Acids Eamentioning
confidence: 99%